Effect of Liuweibuqi capsules on the balance between MMP-9 and TIMP1 and viability of alveolar macrophages in COPD. Issue 5 (19th September 2017) - Wang, Chengyang; Ding, Huanzhang; Tang, Xiao; Li, Zegeng; Gan, Lei
Abstract : The present study aims to investigate the effect of Liuweibuqi (LWBQ) capsules on the expression of matrix metalloproteinase (MMP)-9 and TIMP1 and cell viability of alveolar macrophages (AMs) in chronic obstructive pulmonary disease (COPD). Rats were randomly divided into normal control (NC) group, model control (MC) group, Jinshuibao (JSB) group, spleen aminopeptidase (PAT) group, and low dose of LWBQ (LWBQ low), mid dose of LWBQ (LWBQ mid), and high dose of LWBQ (LWBQ high) group ( n =10). Lung function was measured with a spirometer. Serum cytokines including tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were detected using ELISA. The expressions of MMP-9 and TIMP1 were detected by quantitative real-time PCR (qRT-PCR) and Western blot. MTT assay and flow cytometry were used to measure cell viability and apoptosis. Compared with the NC group, body weight and lung function were reduced in the MC group. In addition, the serum levels of IL-6 and TNF-α were higher in the MC group than those in the NC group. The expression of MMP-9 protein in the AMs from rats was higher, and TIMP1 protein was lower in the MC group compared with the NC group. After LWBQ capsules treatment, compared with the MC group, the expression of inflammatory cytokines and MMP-9 were lower and TIMP1 was higher. Moreover, after LWBQ-medicated serum treatment, the release of inflammatory cytokines was reduced from AMs. Besides, LWBQ-medicated serum decreased the expression of MMP-9 and increased the expression of TIMP1 and cell viability compared with those in MC group. In conclusion, LWBQ capsules can inhibit the release of inflammatory cytokines, promote cell viability in AMs, and regulate the expression of MMP-9 and TIMP1.